Outcomes following total femur resection and modular endoprosthetic replacement for primary bone tumours - Wan Ismail, Wan Mohd Faisham; Sharifudin, Mohd Ariff; Wan , Zulmi; Halim, Ahmad Sukari; Mat Zin, Nor Azman; Wan Sulaiman, Wan Azman (2014)
Introduction: Total femur endoprosthesis is an alternative reconstruction option following resection for massive malignant bone tumour with intramedullary extension or skip lesions. Methodology: We reviewed cases with primary bone tumours underwent total femur resection and replacement with megaprosthesis at our centre for the past 15 years. Results: Nine patients were included in our review. Mean age of patients was 21.3 years (range 12 to 35 years old). Seven had osteosarcoma of the femur and two were results of salvage procedure for implant loosening following distal femoral replacement. Another patient underwent surgery for revision of total femur allograft. Free oncologic margins were achieved in all patients. Four patients required vascularised latissimus dorsi free flaps cover for reconstruction of soft tissue defects. The average follow-up was 137 months, ranging from 24 to 180 months. Seven patients were still alive on their last follow up. Six of them being disease free and one survived with presence of pulmonary and contralateral femur metastases. Two patients were complicated with infections, two had stiff knee joint, and one case of peroneal nerve palsy. Excellent or good functional outcomes obtained in all patients on their last follow up in accordance to Musculoskeletal Tumor Society (MSTS) Scoring System. Conclusion: Modular endoprosthetic replacement is a good reconstruction option in selected cases. It provides early stability and good functional outcomes. However, it is a technically demanding procedure.